2012
DOI: 10.1021/jp3093868
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Structures Loading with an Anticancer Compound As Drug Delivery Systems

Abstract: Two different structures of zeolites, faujasite (FAU) and Linde type A (LTA), were studied to investigate their suitability for drug delivery systems (DDS). The zeolites in the sodium form (NaY and NaA) were used as hosts for encapsulation of α-cyano-4hydroxycinnamic acid (CHC). CHC, an experimental anticancer drug, was encapsulated in both zeolites by diffusion in liquid phase. These new drug delivery systems, CHC@zeolite, were characterized by spectroscopic techniques (FTIR, 1 H NMR, 13 C and 27 Al solidstat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
90
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 51 publications
4
90
1
Order By: Relevance
“…There are numerous examples of zeolite applications reported in the literature including the heterogeneous catalysis [1,2], polymer catalytic degradation [3], for processes in magnetic resonance imaging [4], in water treatment by biosorption systems [5] as antibacterial materials [6], sensors [7] and drug delivery systems (DDS) [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous examples of zeolite applications reported in the literature including the heterogeneous catalysis [1,2], polymer catalytic degradation [3], for processes in magnetic resonance imaging [4], in water treatment by biosorption systems [5] as antibacterial materials [6], sensors [7] and drug delivery systems (DDS) [8].…”
Section: Introductionmentioning
confidence: 99%
“…For the first 72 h days, it is observed that the PVDF composite samples do not inhibit cell adhesion and promote cell proliferation. So, these PVDF composite renders attractive possibilities for biological and biomedical applications, such as drug delivery [46], cell culture [46] and antibacterial functions [47], among others.…”
mentioning
confidence: 99%
“…Moreover, based on the results obtained in various tumor cells and in tumor bearing animals, the zeolites have shown that they can be successfully applied as adjuvants in anticancer therapy. Anticancer drugs have been loaded into the pores of zeolite and have shown a noticeable cytotoxic effect when applied to cancer cells [61,62]. In these works, zeolite Y (FAU), zeolite A (LTA) [61] and zeolite Beta (BEA) [62] were used as hosts for releasing the anticancer drug.…”
Section: Zeolite For Antimicrobial and Medical Applicationsmentioning
confidence: 99%
“…Anticancer drugs have been loaded into the pores of zeolite and have shown a noticeable cytotoxic effect when applied to cancer cells [61,62]. In these works, zeolite Y (FAU), zeolite A (LTA) [61] and zeolite Beta (BEA) [62] were used as hosts for releasing the anticancer drug. Results showed that zeolites alone reveal no toxicity to cancer cells, while, importantly, anticancer drug-zeolite led to an inhibition of cell viability up to 585-fold when compared to the non-encapsulated drug.…”
Section: Zeolite For Antimicrobial and Medical Applicationsmentioning
confidence: 99%